Comment on "bi-functional Li2 B12 H12 for energy storage and conversion applications: Solid-state electrolyte and luminescent down-conversion dye" by J. A. Teprovich Jr, H. Colón-Mercado, A. L. Washington II, P. A. Ward, S. Greenway, D. M. Missimer, H. Hartman, J. Velten, J. H. Christian and R. Zidan,: J. Mater. Chem. A, 2015, 3, 22853 - Paskevicius, Mark; Jakobsen, A.S.; Bregnhøj, M.; Hansen, B.R.S.; Møller, K.T.; Ogilby, P.R.; Jensen, T.R. (ROYAL SOC CHEMISTRY, 2019)
The photoluminescent properties of selected metal closo-boranes have been assessed. Group 3 elements Sc, Y, and La as well as Li, Na, and Eu-based B 10 H 102- and B 12 H 122- compounds displayed photoluminescence in the ultraviolet (emission λ max ≈ 350 nm) that was not visible to the human eye, in contrast to previous reports. We attribute these earlier results to arachno-borane impurities, which are more readily observed due to their longer wavelength emission spectra.